An Input-Output Analysis for Manpower Requirements: Prospect of Malaysia's Construction Sector - Lelchumanan, Bawani (Malaysian Journal of Business and Economics (MJBE), 2019)
Abstract Manpower planning determined in the process of estimating or projecting the number of labour required for a particular period in the selected sectors or projects in the chosen country. This article presents an exhaustive review of manpower requirements in the construction sector for the year 2020 in Malaysia, in the line with issues arising in Malaysia's construction sector. Using the Input-Output table, the forecast of manpower planning based on the data of four selected construction subsectors in Malaysia, mainly residential building, non-residential building, civil engineering and specialised construction activities. The employment categories based on skilled, medium-skilled and low-skilled labour categorised in The Eleventh Malaysia Plan (2016 - 2020). The most obvious finding to emerge from this study is skilled and low-skilled labour is high in need for all construction subsectors for the year 2020. Malaysia has a high expectation of workforce energy in the construction sector and expects the majority of the construction works handled by the local labour.